Effects of 30 Years of Crop Rotation and Tillage on Bacterial and Archaeal Ammonia Oxidizers. Issue 3 (1st May 2016) - Munroe, Jake W.; McCormick, Ian; Deen, William; Dunfield, Kari E.
Abstract : Ammonia‐oxidizing bacteria (AOB) and archaea (AOA) both mediate soil nitrification and may have specialized niches in the soil. Little is understood of how these microorganisms are affected by long‐term crop rotation and tillage practices. In this study, we assessed abundance and gene expression of AOB and AOA under two contrasting crop rotations and tillage regimes at a 30‐yr‐old long‐term experiment on a Canadian silt loam soil. Continuous corn ( Zea mays L.) (CC) was compared with a corn–corn–soybean [ Glycine max (L.) Merr.]–winter wheat ( Triticum aestivum L.) rotation under‐seeded with red clover ( Trifolium pretense L.) (RC), with conventional tillage (CT) and no‐till (NT) as subplot treatments. Soil sampling was performed during the first corn year at four time points throughout the 2010 season and at three discrete depths (0–5, 5–15, and 15–30 cm). Overall, AOA abundance was found to be more than 10 times that of AOB, although AOA transcriptional activity was below detectable levels across all treatments. Crop rotation had a marginally significant effect on AOB abundance, with 1.3 times as many gene copies under the simpler CC rotation than under the more diverse RC rotation. More pronounced effects of depth on AOB abundance and gene expression were observed under NT versus CT management, and NT supported higher abundances of total archaea and AOA than CT across the growing season. We suggest that AOB may be more functionally important than AOA in this high‐input agricultural soil but that NT management can promote enhanced soil archaeal populations. Core Ideas: No‐till showed a trend of higher archaeal and AOA abundance across growing season. AOA were on average more than 10‐fold more abundant than AOB. Expression of archaeal amoA gene was undetected in neutral pH agricultural soil. Abundance and gene expression of AOB, but not AOA, decreased with soil depth.